Health risk assessment of cadmium, chromium and nickel from car paint dust from used automobiles at auto-panel workshops in Nigeria - Nduka, John Kanayochukwu (Toxicol Rep, 2019)
Nigeria’s economic problems which inhibited local production has resulted in massive importation of used automobiles. Most of these automobiles need some repairs and reworking, having outlived their lifespan in the manufacturer’s country. This study centers on the human carcinogenic and non-carcinogenic health risk assessment of cadmium, chromium and nickel exposures from reworking of imported used vehicles. Scraped car paint dusts from 56 Japanese made cars were collected from 8 different panel beating (body works) workshops (A–H) in Southeastern Nigeria. They were homogenized, mixed, divided into fine particles, filtered and digested by standard method. The filtrates were assayed for cadmium, chromium and nickel with atomic absorption spectrophotometry (AAS, 200A), workshops F and D have the highest concentration (mg/kg) of Cd (3.58 ± 0.02) and (3.36 ± 0.04) and higher than levels in workshops A, B, C, E, G and H. Chromium (mg/kg) in workshops F and G were (2.87 ± 0.04) and (2.95 ± 0.06) and higher than the other workshops. Nickel in workshop A (3.84 ± 0.04) is close to other workshop values. The highest hazard quotients for adults were cadmium in workshops B (1.37E-01), D (1.69E-01), E (1.79E-01) (inhalation), chromium [workshops G (5.45E-02), F (5.29E-02) and C (5.24E-02) inhalation]. Nickel -workshop A (5.9E-03) for children (inhalation). HQ in children through ingestion is cadmium (3.72E-04) workshop F and ingestion- 3.21E-01(workshop F) while nickel is 1.06E-02 (workshop A).The highest cancer risks were in exponents -4,-7 and -8 (adult) and -3, -6 and -9 (children) for workshops A–H through inhalation, ingestion and dermal contact, exposures to scrap car paint dust may be of significant public health importance in Nigeria as it can add to body burden of some carcinogenic heavy metals.